Accessions during the Year - Anonymus, A. (1966)
Report to the Visitors 1965; i.a. Luristan bronzes (see pl. III), Neo-Babylonian stamp seal, Achaemenian polychrome chalcedony scaraboid; pottery from NW Persia and Anatolia (see pl. II and p. 8); terracotta model bed with a naked female figure reclining on it, probably Elamite, c. 13th century B.C.